Dynamic contrast-enhanced computed tomography in the treatment evaluation of patients with colorectal liver metastases treated with ablation: a feasibility study. (August 2019) - Andersen, Iben R; Thorup, Kennet; Jepsen, Betina N; Mortensen, Frank V; Nielsen, Dennis T; Rasmussen, Finn
Background: A major concern following ablation treatment is the risk of insufficient heating leaving vital tumor tissue at the treatment site, leading to recurrent disease and reduced survival. Dynamic contrast-enhanced computed tomography (DCE-CT) has the potential to evaluate the treatment site in an objective and standardized manner and provide a marker of recurrent disease. Purpose: To evaluate the feasibility of measuring changes in the dynamic parameters of the treatment site following ablation of colorectal liver metastases, assessed by DCE-CT using a novel evaluation method, applying a circumferential semi-automated attenuation-restricted volume of interest (VOI). Material and Methods: Forty-three treatment sites following ablation in 39 patients with colorectal liver metastases were evaluated using DCE-CT. A total of 159 DCE-CT scans were analyzed using the circumferential semi-automatized VOI. Results: We found no significant differences in the dynamic parameters over time between a group of patients with recurrent disease and a group without. No consistent associations between time to recurrence and the dynamic histogram parameters were identified. Conclusion: In this exploratory feasibility study, we were not able to differentiate between the two groups (recurrence/no recurrence) using the dynamic parameters derived from the standardized circumferential VOI. In time, the method may have potential to evaluate the treatment site following ablation in an objective and standardized manner. Currently, the method needs further refinement before clinical implementation.